Political Elites And Society: Development Efforts and Increasing Community Participation in Sekapuk Village Tourism Development during the Covid-19 Pandemic - Setiadi, Ozi (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2022)
Political elites have a role in exploring the potential and improving the community's economy. This study aims to discuss the role of village political elites in increasing development and community participation, especially Selo Tirto Giri (Setigi) tourism. As well as knowing the impact of Setigi tourism for the community during the Covid-19 pandemic. The research method in this research is qualitative with descriptive analysis. Data obtained through direct observation and literature study. This study proves that the village political elite, through democratic principles, invites the community to participate in the development of Setigi tourism. Efforts to increase community participation are carried out by inviting them to become Taplus Invest investors in the form of saving Rp. 8,000 per day until Rp. 2,400,000 is collected, which is converted into one share certificate. The Sekapuk Village Government also invites the community directly in dredging garbage in the limestone hills for 1 year. The existence of Setigi tourism is an alternative source of income for the community in addition to their main livelihood. During the Covid-19 pandemic, Setigi tourism also experienced a decline in visitors, but was still able to survive.